2005
DOI: 10.1086/427996
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliStrains Belonging to Phylogenetic Group B2 Have Superior Capacity to Persist in the Intestinal Microflora of Infants

Abstract: Escherichia coli strains segregate into 4 phylogenetic groups, designated "A," "B1," "B2," and "D." Pathogenic strains belong to group B2 and, to a lesser extent, group D, which more frequently carry virulence-factor genes than do group A strains and group B1 strains. This study investigated whether the capacity of E. coli to persist in the human intestine is related to its phylogenetic type. Resident (n=58) and transient (n=19) commensal E. coli strains isolated during a longitudinal study of 70 Swedish infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
158
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 35 publications
19
158
1
Order By: Relevance
“…Moreover, the latter predominate among E. coli strains with the ability to survive in the environment (Walk et al, 2007). By contrast, group B2 are more likely to be host-adapted, 'specialists' (Gordon & Cowling, 2003;Nowrouzian et al, 2005;White et al, 2011), and at least some B2 strains appear to be regular human commensals (Clermont et al, 2008;Carlos et al, 2010). Therefore, a larger number of TA loci in groups A and B1 may reflect their higher stress tolerance, and hence adaptation to various ecological niches (Pandey & Gerdes, 2005;Wang & Wood, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the latter predominate among E. coli strains with the ability to survive in the environment (Walk et al, 2007). By contrast, group B2 are more likely to be host-adapted, 'specialists' (Gordon & Cowling, 2003;Nowrouzian et al, 2005;White et al, 2011), and at least some B2 strains appear to be regular human commensals (Clermont et al, 2008;Carlos et al, 2010). Therefore, a larger number of TA loci in groups A and B1 may reflect their higher stress tolerance, and hence adaptation to various ecological niches (Pandey & Gerdes, 2005;Wang & Wood, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, a number of authors have sought to establish the prevalence of E. coli with ExPEC potential colonising the gut by performing microbiological screening studies on the stool of healthy individuals that delineate resident E. coli strains based on their phylogroup (58)(59)(60)(61)(62)(63). Results of these studies have demonstrated that 11-48% of healthy individuals are colonised with E. coli belonging to phylogroup B2, which is traditionally associated with virulence and ExPEC infections.…”
Section: Expec As An Intestinal Colonistmentioning
confidence: 99%
“…This collection could provide information on the occurrence and prevalence of integrons before the misuse and overuse of antimicrobials -major contributors to the development and spread of resistance [17]. Another set (40) was isolated in 2009 from urine of women with clinical and laboratory diagnoses of community-acquired urinary tract infections in Belo Horizonte, Brazil [18]. This study was approved by Ethics Committee UFMG (178/09).…”
Section: Bacterial Strainsmentioning
confidence: 99%